Exploring the Impact of Economic Structure on Carbon Emissions: A Case Study of Pakistan - Khalid, Muhammad Hasnain; Haq, Ihtisham ul; Khan, Dilawar; Abbas, Khurram (International Journal of Energy Economics and Policy, 2022)
Climate change has marked its effects on Pakistan in form of different problems like floods, droughts, change in crop patterns, heat waves, changes in weather conditions and health issues. One of the reason of climate change is environmental degradation that’s why several studies are conducted in case of Pakistan to examine the factors of environmental degradation. This study also explores the factors of environmental degradation for Pakistan and is unique study as so for none of the empirical studies conducted in context of Pakistan analyzed the effect of economic structure on environmental degradation. So, the prime objective of this study is to explore the impact of economic structure on environmental degradation. The economic structure for Pakistan’s economy is being captured through agriculture, industrial and service sector over the years. As energy and trade openness grab attention from researchers in examining factors of environmental degradation thus; energy consumption and trade openness are introduced in the study model as control variables. Once order of integration of time series data is determined, long run relationship is found through bound testing approach. Agricultural and service sector are found to have negative impact on environmental degradation but; service sector has insignificant effect on environmental degradation. The industrial sector is aggravating environmental degradation in long run but; is abstaining environmental degradation in short run. Hence; the different effect of industrial sector on environmental degradation in long run and short run is providing the opportunity for policy makers to come up with different policy measure for long run and short run. Energy is found to have positive and significant effect on environmental degradation in both time spans whereas trade openness has negative and significant effect on environmental degradation in long run. Policy implications are suggested on basis of findings of this study for Pakistan.